Training needs of agriculture extension officers in Iraq - Saleh, Jasim Mohammed (International Journal of Scientific and Research Publications, 2016)
This paper examines the training needs of extension agents in Iraq agriculture, specifically, the practice of different extension approaches, activities, methods and principal problems of extension agents in their fieldwork. Training in any form is intrinsic to organizational effectiveness and efficiency training. The type of training given to an individual who is gainfully employed but requires certain knowledge and skills to improve his efficiency. The purposes of this paper are 1) investigating the training needs for extension agents to perform their work effectively, 2) suggesting the suitable extension method for the present agricultural extension service in Iraq, and 3) identifying the primary functions and major problems of extension agents in Iraq 4) identifying the training needs in these study according to the areas of studies. In-service training of the Extension Agents is the call of the time. Training needs were assessed using the Borich Needs Assessment Model, This Model is designed around the skills individuals and groups need to be effective in the future and are used for making human resources decisions. Through trained Agricultural Extension Agents new agricultural technology can easily and favorably be transferred to clientele. According to the centralized administration, the extension workers have being practicing mostly the training and visit system in a top-down Iraq. Due to the non-involvement of local people in the extension program planning, implementation, and decision-making process, the extension service developed inefficiently. Therefore, the extension workers, researchers, and local farmers should cooperate in the extension work, especially in the planning, implementation, and evaluation of the extension program to develop the extension service in Iraq Agriculture. The local farmers should be involved in the decision-making process because they are really facing the problems in their field. All extension workers and subject matter specialists are now interested in implementing PEA in the future in the agricultural extension service.